Calculation of steel-reinforced concrete structures made of cold-formed steel profiles under biaxial loading - Drobotia, Oleksandr; Vakhnenko, Hennadii (Academic journal Industrial Machine Building Civil Engineering, 2025)
The aim of the work is to establish theoretical dependences for determining stresses at the extreme points of the cross-section of steel-reinforced concrete rod structures made of cold-formed steel profiles under biaxial bending loading. The steel part of the cross-section of the rod under consideration is a U-shaped profile, which is filled with concrete. At the first stage of manufacturing a prestressed rod, an initial bending of the steel part of the beams opposite to the operational one is created using mechanical jacks. During concreting of the U-shaped cavity and for the period of setting of the concrete to the design strength, the jacks under the steel beams remain. At the live load (third stage), the combined steel-concrete cross-section works together. In the concrete part, deformations develop from the undeformed (zero) state, while in the steel part, deformations of the normal cross-section are superimposed on the already existing deformations opposite to the operational ones obtained at the first stage of the combined structure during its manufacture.
Keywords: steel-reinforced concrete; cold-formed steel profiles; rod; biaxial load; strain